ILB 938, a valuable faba bean (Vicia faba L.) accession. Issue 5 (6th August 2018) - Khazaei, H.; Link, W.; Street, K.; Stoddard, F. L.
Abstract: Here we review the potential of ILB 938 (IG 12132 – doi: 10.18730/60FD2), a unique faba bean accession originating from the Andean region of Colombia and Ecuador, maintained at ICARDA – International Center for Agricultural Research in the Dry Areas, with resistance to multiple biotic and abiotic stresses and carrying some useful morphological markers. It has been used as a donor of leaf-related drought adaptation traits and chocolate spot ( Botrytis fabae ) resistance genes in faba bean breeding programmes worldwide. From generated populations of recombinant inbred lines, quantitative traits loci associated with these useful traits have been mapped. Other markers, such as a lack of stipule-spot pigmentation and clinging pod wall, show the presence of unusual changes in biochemical pathways that may have economic value in the future.